Material choices for triboelectric nanogenerators: A critical review - Zhang, Renyun; Olin, Håkan (EcoMat (Beijing, China), 2020)
A triboelectric nanogenerator (TENG) is a novel technology with applications in many areas, including energy harvesting, self‐powered sensing, medication, and electronics. The materials used as triboelectric layers are diverse and include polymers, metals, and inorganic materials. The most commonly used materials are dielectric polymers such as PTFE, FEP, PDMS, and Kapton. Green materials, such as cellulose‐based materials, have recently gained increasing interest, and the performance of TENGs using cellulose materials has improved. The material choices are of great importance for TENGs since the triboelectric effects of the materials are fundamental for TENGs. To design a TENG for a particular application, several parameters need to be considered, such as power density, stability, flexibility, and sustainability. This critical review will summarize and evaluate the material choices for TENGs in different applications. The material choices for triboelectric nanogenerators (TENGs) are reviewed and evaluated, showing the mechanisms behind the choices where the choices of the material pairs could significantly influence the electrostatic induction process of the TENGs.